Hybrid perovskite films by a new variant of pulsed excimer laser deposition: a room-temperature dry process - Bansode, Umesh P.; Naphade, Rounak; Game, Onkar S.; Agarkar, Shruti A.; Ogale, Satishchandra (Journal of Physical Chemistry C, 2015)
A new variant of the classic pulsed laser deposition (PLD) process is introduced as a room-temperature dry process for the growth and stoichiometry control of hybrid perovskite films through the use of nonstoichiometric single target ablation and off-axis growth. Mixed halide hybrid perovskite films nominally represented by CH(3)NH(3)PbI(3-x)A(x) (A = Cl or F) are also grown and are shown to reveal interesting trends in the optical properties and photoresponse. Growth of good quality lead-free CH3NH3SnI3 films is also demonstrated, and the corresponding optical properties are presented. Finally, perovskite solar cells fabricated at room temperature (which makes the process adaptable to flexible substrates) are shown to yield a conversion efficiency of about 7.7%.

Highly stable laser-scribed flexible planar microsupercapacitor using mushroom derived carbon electrodes - Yadav, Poonam; Basu, Aniruddha; Suryawanshi, Anil; Game, Onkar S.; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
A report is presented on the fabrication of all solid-state interdigitated flexible microsupercapacitor using ultrafast and highly scalable laser scribing technique, using highly mesoporous carbon synthesized from biomass (mushroom) with hydrothermal preprocessing. The specific protocol used for carbon synthesis renders some unique property features to the material (surface area of 2604 m(2) g(-1) with hierarchical pore size distribution) in the context of supercapacitor electrode application. A polyvinyl alcohol (PVA)-H2SO4 gel electrolyte is used for electrochemical measurements. The microsupercapacitor shows high cyclic stability up to 15000 cycles. Moreover it shows nearly 90% stability after 1000 bending cycles at 60 degrees angle. It also retains its performance even under 120 degrees bending condition. This work represents a facile and fast technique for microscaled device fabrication that can be easily commercialized. Moreover, the mushroom-derived carbon used to make the electrodes holds great promise in context of the stability and flexibility of flexible supercapacitors.